Behaviour management and the role of the teaching assistant a guide for schools - Clarke, Emma, (Writer on education) (New York, NY : Routledge, 2021)
Behaviour Management and the Role of the Teaching Assistant draws on the latest research as well as teaching assistants' own views to enable readers to reconsider TA deployment and to maximise the benefits TAs have to offer in supporting children's behaviour. It considers the difficulties facing TAs, summarises the key stages in the evolution of their role in the classroom and highlights the significant challenges of TAs' role definition. Using current research findings, this book provides guidance and practical activities to support schools in empowering TAs to work with children whose behaviour challenges. Each chapter considers a range of strategies for working with TAs, as well as the strengths and limitations of these approaches. There are also a range of self-/school-auditing and self-evaluation tasks with key points to consider and practical in-school suggestions at the end of each chapter. This is essential reading for professionals at all levels working in schools wanting to understand how teaching assistants can best be supported to successfully manage behaviour in schools.
Introduction Part One Who are TAs and What Do they Do? Behaviour in Primary Schools Perspectives on Behaviour Approaches to Managing Behaviour How and why the TA role is changing and what this might mean for schools today TAs Supporting Children's Behaviour - Advantages and Limitations TAs, Teachers and School Behaviour Policies Part One Conclusion Part Two 8. Clearly Defined TA role and its Impact on Managing Behaviour 9. Others' Views of the TA Role and their Impact on TAs Part Two Conclusion Part Three 10. Training and the TA 11. Power and the TA 12. Whole-School Approaches and the TA 13. Deployment and the TA Part Three Conclusion Part Four 14. Empowering TAs to Work with children Part Four Conclusion
OCLC-licensed vendor bibliographic record.
Keywords: Teachers' assistants -- Education (Elementary); Classroom management; Behavior disorders in children; Behavior modification; EDUCATION / General